Investigate the link between workplace dynamics and job satisfaction among Saudi pharmacists - Saleha Iqbal; Syeda Samreen Fatima; Faiza Zubair; Asma Imran; Surayya Jamal; Abdul Malik Mujahid; Gurumurthy Ramaiah; Mustafa Al-Hamzi (Journal of Pharmaceutical Policy and Practice, 2025)
Background: Job satisfaction is a critical factor influencing employee performance, motivation, and retention in healthcare, particularly among pharmacists. Positive workplace relationships and psychological well-being are essential contributors to job satisfaction, yet little is known about how these dynamics function in Saudi Arabia. This study investigates the link between workplace relationships and job satisfaction among Saudi pharmacists. It examines psychological well-being as a mediator and personality traits as a moderator in this connection.Method: A cross-sectional quantitative design was adopted. Data were collected from 384 licensed pharmacists in Tabuk, Saudi Arabia, by using the Workplace relationship quality questionnaire (WRQ), Job satisfaction survey (JSS), Positive and negative affect schedule (PANAS), and HEXACO personality inventory. SPSS and Hayes’ PROCESS macro were used for statistical analysis.Results: Workplace relationships positively correlated with psychological well-being (r = .52, p < .01) and job satisfaction (r = .45, p < .01). Mediation analysis confirmed psychological well-being fully mediated the connection between workplace relationships and job satisfaction (β = 0.23, 95% CI [0.12, 0.34]). Conscientiousness negatively moderated this connection (β = −0.18, p = .005).Conclusion: The findings underscore the importance of cultivating strong workplace relationships and promoting psychological well-being to enhance pharmacist job satisfaction. Personality traits should also be considered in workforce planning to optimise job fit and satisfaction.